TYPIFICATION OF SRI LANKAN GESNERIACEAE - Ranasinghe, S.; Middleton, D. J.; Atkins, H. J.; Milne, R.; Möller, M. (Edinburgh Journal of Botany, 2019)
Towards a comprehensive revision of Gesneriaceae in Sri Lanka, 12 names are here typified, of which 11 are lectotypifications, including one second-step lectotypification, and the other is a neotypification.